Potency of Micro Hydro Power Plant Development Use of Kelampuak River Flow Located in Tamblang Village – Buleleng - Putra Negara, Dewa Ngakan Ketut (Jurnal Energi Dan Manufaktur; Vol 3, No.2 Oktober 2009)
Need of electrical energy is increasing along with people population and economic growth. According to PLN data, Bali Province’s electrical consumption is predicted growth 5,6% in average every year. Until year 2007, electrical condition in Bali is categorized critical. If Power Plat in Bali, PLTG Gilimanuk that has power 130 MW is out of system, affecting Bali’s electrical back up is minus. Consecuenlly, it will be extinguishing if there is not adding power plan or new energy supply. This problem needs to be anticipated by use of thermal energy program such as coal, gas and geothermal and use of alternative energy such as solar, wind and ocean energies. Regency of Buleleng is one of Regency in Bali having potency of renewable energy development especially water resource. It has some rivers that have potency to be developed as a Micro Hydro Power Plant (PLTMH). One of them is Kelampuak River which is located in Tamblang Village. As a first step in developing of Micro Hydro Power Plant, it needs to be known water debit and head of the river. For that reason, it needs to be investigated debit and head of Kelampuak River so that it can be predicted the power can be generated.
Keywords: Micro Hydro Power Plan, Alternative energy, Renewable energy